Visions for the future: Towards more vibrant, sustainable, and smart cities - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2024)
With reference to Singapore's smart urban initiatives, this book provides insights into how urban planning, digital technology and sustainability issues are impacting people and businesses.The chapters are loosely structured with regards to key dimensions of smart cities such as urban innovation spaces; open innovation ecosystems; smart manufacturing; undergraduate education with regards to A.I. readiness, gamified leadership & team-building skills, and digital sustainability; ESG, environmental handprint, workplace sustainability and climate resilience; pillars of successful aging & inclusiveness; and smart city management challenges.How does Singapore develop vibrant urban innovation spaces? In what ways can living labs create sustainable impact? How can SMEs benefit from the adoption of Industry 4.0? What is the role of chatbots in making undergraduate students 'AI-ready'? How does gamification help learners to acquire leadership and team-building skills? Why is digital sustainability important and how can educators sensitize youths toward cultivating more sustainable ways of living? What is the business case for ESG (environmental, social, and corporate governance) stewardship? How to steer Singapore's built environment towards a sustainable future? How to connect companies and help them to combat climate change by regenerating our planet? How to induct new employees to an organization and acclimatize them to the company's culture of sustainability, job roles and workplace sustainability? How to enable smart(er) aging? What is the future of inclusive smart cities? What are some of the opportunities for more theory-based, empirical research on smart city management challenges from a purpose-driven business perspective linked to human betterment? These questions and more are addressed in this book.Visions for the Future is a complementary reading resource suitable for anyone interested in understanding how the concept of Smart Cities can improve lives and livelihoods for all in a sustainable manner — from undergraduate and graduate students to smart city stakeholders in business and society as well as educators and municipal leaders.